(untitled) - Minnaar, Phillipus Petrus

Microclimate and grape ripeness effects on the phenolic composition of grapes and wine (Vitis vinifera L. cv. Shiraz/101-14 Mgt) (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.